Study of the fungal enzyme production by cultured in basidiomycetes lignocellulosic residues - Zancan, Luiza Rodrigues; Barreto, Andressa Ribas; Menezes, Cristiano Ragagnin de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Lignocellulosic residues are largely generated by agricultural activities, and much of this material is not used, being transformed into polluting the environment. For occurs the use of lignocellulosic residues, was studied biodegradability of these substrates by fungi Basidiomycetes, by enzymatic activity. The strains Pleurotus sp 001 (P001) and Pleurotus sp 068 (P068), were grown on sugarcane bagasse, through solid state fermentation, incubated in greenhouses to 30 degrees C for periods of 15, 30, 45, 60, 75 and 90days. The production of cellulolytic enzymes occurred with discrete values in the studied conditions. However, for the ligninolytic enzyme activity, the maximum activity of the manganese peroxidase enzyme was observed in high (18.67 U/L at day 60 of incubation). The strains P001 and P068 shown promise in the use of lignocellulosic substrates for enzyme production. However, more detailed studies are needed so that the optimal conditions of production of these enzymes by strains studied are obtained.